Linkages between Oil Sectors Returns of Asian Emerging Stock Markets: Unearthing the Hidden Opportunity for Portfolio Diversification - Pavto, Velip Suraj; Raju, Guntur Anjana (International Journal of Energy Economics and Policy, 2020)
The increase in the extent of integration between global markets declined the opportunity for international portfolio diversification. This in turn created the hurdles amongst the investors and therefore recently they either prefer less correlated emerging markets or asset allocation at sectoral level. In view of this, considering Asian emerging markets at the forefront of portfolio diversification venue globally, this research aims at examining the linkages and portfolio diversification prospects across the oil sectors of eight Asian emerging stock markets. The study used VAR based Causality/Block Exogeneity Wald test and Forecast Error Variance Decomposition to investigate the data period of January 01, 2004, to August 31, 2019. The results exhibited a weak form of linkages between Asian emerging markets oil sector indices and therefore, it would be a great platform for the portfolio managers and investors to reap diversification benefits in this region. Keywords: Oil sectors of Asian emerging stock markets, VAR, linkages, portfolio diversification JEL Classifications: G11, G15 DOI: https://doi.org/10.32479/ijeep.9970